Body roundness index, thyroid hormones, and threshold effects in US adults: a cross-sectional study from NHANES - Yang, Sijia; Liao, Kun; Zhou, Lu; Zhang, Shengbo; Wu, Jianchao (Frontiers in Nutrition, 2025)
BackgroundThe correlation between visceral adipose tissue and thyroid hormones is debated, and the conventional body mass index (BMI) is insufficient for differentiating fat distribution patterns. This study investigates the nonlinear relationship and threshold effects of the Body Roundness Index (BRI), a geometric metric of visceral fat (BRI = 364.2–365.5 × [1 – (waist circumference/2π)2/(0.5 × √height)2]), on thyroid hormone levels, hypothesizing that BRI influences thyroid hormone concentrations through a specific threshold.MethodsThis study analyzes cross-sectional data from 10,086 participants in the National Health and Nutrition Examination Survey (NHANES) obtained between 2007 and 2012. Participants underwent anthropometric measurements and thyroid hormone assessments. We employed multiple linear and piecewise regressions to examine associations between BRI and the following thyroid hormones: free triiodothyronine (FT3), total triiodothyronine (TT3), free thyroxine (FT4), total thyroxine (TT4), and thyroid-stimulating hormone (TSH). We assessed nonlinearity and threshold effects and reported 95% confidence intervals and p-values.ResultsThe median age of participants was 43 years, with a BRI ranging from 0.77 to 19.33. After adjustments, a positive correlation was found between BRI and both TT3 (β = 0.95, 95% CI: 0.68–1.23) and TT4 (β = 0.06, 95% CI: 0.04–0.08). In contrast, a negative correlation was observed between BRI and FT4 (β = –0.03, 95% CI: –0.04 to –0.01). Threshold analysis revealed that when BRI was below 7.21, FT3 and TT3 increased with rising BRI, but this effect weakened or reversed beyond this threshold.ConclusionIn the American population, BRI is associated with non-linear relationships and threshold effects regarding thyroid hormone levels. Positive correlations exist between BRI and TT3/TT4, while a negative correlation is noted with FT4. Moreover, the dynamic threshold effect of BRI on FT3 and TSH indicates that visceral fat distribution characteristics should be considered when evaluating thyroid hormones.